2014
DOI: 10.1016/j.jaad.2013.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of morphea after successful ultraviolet A1 phototherapy: A cohort study

Abstract: Background Studies support efficacy of ultraviolet A1 (UVA1) phototherapy, but little is known about recurrence after successful UVA1 treatment. Objective Determine the frequency of recurrent activity after UVA1 phototherapy and variables associated with recurrence. Methods Case series and prospective cohort study of patients treated with UVA1 phototherapy with minimum 6 months follow-up. Demographics, clinical features, and cumulative UVA1 dose were analyzed for association with recurrence. Results Of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 27 publications
4
41
1
9
Order By: Relevance
“…Whether patients with darker skin respond less to UVA1 phototherapy is still a matter of debate . Moreover, it has been shown that within 3 years after therapy, about 50% of patients treated with UVA1 experience recurrences . In these cases, a second cycle of UVA1 phototherapy should be considered.…”
Section: Localized Scleroderma (Morphea)mentioning
confidence: 99%
“…Whether patients with darker skin respond less to UVA1 phototherapy is still a matter of debate . Moreover, it has been shown that within 3 years after therapy, about 50% of patients treated with UVA1 experience recurrences . In these cases, a second cycle of UVA1 phototherapy should be considered.…”
Section: Localized Scleroderma (Morphea)mentioning
confidence: 99%
“…MF ve AD'de olduğu gibi, lokalize sklerodermada da UVA1 ile başarılı tedavi sonrası nüks olabilmektedir. UVA1 tedasivine yanıt veren 37 hastanın %46'sında, tedavi bitiminden ortanca 10,8 ay sonra nüks olduğu gözlenmiştir (75). UVA1'in, ekstragenital liken skleroz, sistemik skleroz, sklerodermoid Graft Versus Host hastalığı ve nefrojenik sistemik fibroziste de etkili olduğuna dair çeşitli yayınlar bulunmaktadır (76,77).…”
Section: Sklerozan Hastalıklarda Fototerapiunclassified
“…In a cohort study of 37 patients with morphea with positive clinical benefits from UVA1 treatment 44.5% recurred at 2 years, and 48.4% recurred at 3 years [52]. There was no difference between medium- (60–90 J/cm 2 ) and high-dose (>90 J/cm 2 ) UVA1 phototherapy with respect to recurrence.…”
Section: Clinical Evidence Of Phototherapy’s Efficacymentioning
confidence: 99%
“…There was no difference between medium- (60–90 J/cm 2 ) and high-dose (>90 J/cm 2 ) UVA1 phototherapy with respect to recurrence. There was a 1.15-times higher chance of disease recurrence for an increment of 1 year in duration of morphea prior to UVA1 treatment [52]. …”
Section: Clinical Evidence Of Phototherapy’s Efficacymentioning
confidence: 99%